Efektivitas Read Aloud dalam Pengembangan Bahasa Anak Usia Dini - Aliyah, Rifatul; Fitri, Ruqoyyah; Jannah, Miftakhul; Kristanto, Andi; Adhe, Kartika Rinakit (UNIB Press, 2025)
Language development is crucial in early childhood growth, requiring appropriate stimulation to optimize brain potential during the golden period. The decline in reading interest due to technological advancement has negatively impacted reading comprehension abilities, as demonstrated by the 2016 OECD PISA study ranking Indonesian students' reading abilities at 64th position globally. This study analyzes the effectiveness of the read-aloud method in early childhood language development through comprehensive literature review. This study employed qualitative methodology reviewing 20 scientific articles published between 2020-2025, obtained through Google Scholar. Data analysis utilized content analysis techniques with systematic collection, synthesis, and examination to maintain research validity. Results demonstrate that read-aloud consistently provides positive impacts on various language abilities, including vocabulary enrichment, receptive and expressive language improvement, reading interest cultivation, and oral communication skills development. Effective implementation involves active child-reader interaction, engaging picture books utilization, question-and-answer strategies, and word repetition. Among analyzed articles, majority employed qualitative approaches (10 articles), followed by quantitative methods (6 articles), with highest publication frequency in 2023-2024. Despite demonstrating high effectiveness, research gaps remain regarding method variations for different cultural contexts, insufficient longitudinal studies on long-term impacts, and limited parent-teacher collaboration research. This study concludes that read-aloud is a highly valuable strategy in early childhood education for building strong literacy foundations.